COMPARISON OF PREDICTIVE VALUE OF RISK SCORES REGARDING THE SHORT-TERM AND LONG-TERM PROGNOSIS OF PATIENTS WITH ACUTE MYOCARDIAL INFARCTION TREATED WITH PRIMARY PERCUTANEOUS CORONARY INTERVENTION - Đurošev, Ivana; Kadrić, Esma; Stanković, Goran (Medicinski podmladak, 2020)
Introduction: Primary percutaneous coronary intervention (pPCI) presents standard treatment in patients with acute myocardial infarction. In order to predict the prognosis of patients with ST segment elevation myocardial infarction (STEMI), several risks scores risk have been developed.Aim: We aimed to compare the predictive value of three validated risk scores, regarding intrahospital, short-term (30-days) and long-term (1-year) mortality among patients with a diagnosis of STEMI treated with pPCI in the Catheterization lab, Clinical Center of Serbia.Material and methods: This retrospective study included 311 consecutive patients with a diagnosis of STEMI treated with pPCI in 2017.  Patients with cardiogenic shock at admission were excluded. Data were analyzed from the electronic database. For every patient the value of CADILLAC, ZWOLLE and TIMI score was calculated. The predictive ability of the risk scores was compared by area under (AUC) the ROC (Receiver Operating Characteristic) curves. The short-term and long-term outcome of the patient was assessed by telephone and clinical contact.Results: The study population was 311 patients, with an average age of 61±10 years, of which 237 (76.2%) were male. Rates of intrahospital, mortality at 30 days and at one year after pPCI were 1.9%, 3.2%, 6.1%. All three test scores showed very good predictive value in predicting short-term mortality, both intrahospital (0.962; 0.986; 0.964, p=ns within scores) and after 30 days (0.920; 0.956; 0.861, p=ns within scores), while after 1 year accuracy of CADILLAC and ZWOLLE was better than TIMI score (0.921; 0.905; 0.786, p vs. TIMI 0,0087 and 0,0567). Age, three vessel coronary disease and lower admission hemoglobin were identified as independent predictors for one-year mortality by logistic regression analysis.Conclusion: CADILLAC and ZWOLLE showed very good predictive ability for intrahospital, short and long-term mortality, while for TIMI score, comparable accuracy was observed only for a period up to 30 days following pPCI.Key words: acute myocardial infarction, STEMI, primary PCI, risk assessment
Keywords: acute myocardial infarction, STEMI, primary PCI, risk assessment